1992
DOI: 10.1128/jb.174.3.1060-1062.1992
|View full text |Cite
|
Sign up to set email alerts
|

Replication of the R6K plasmid during the Escherichia coli cell cycle

Abstract: The cell-cycle replication pattern of the R6K plasmid has been investigated by using the membrane-elution technique to produce cells labeUled at different times during the division cycle and scintillation counting for quantitative analysis of radioactive plasmid DNA. The high-copy plasmid R6K replicates exponentially in a cell-cycle-independent manner. A mini-R6K plasmid deleted for the onra origin of replication also replicates, exponentially in a cell-cycle--independent manner. Plasmid R6K is a relatively la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Because a culture of cells is not an amorphous mass of cytoplasm but a distribution of cells at various points of the cell cycle, and because many plasmids are known to attach to the cell membrane either loosely or to perform functions like partition and replication, such models should be used with caution. The results of membrane-elution experiments for high-copy plasmid replication during the cell cycle (Keasling et al, 1991(Keasling et al, , 1992bLeonard and Helmstetter, 1988;Zeuthen et al, 1972) and models, such as the one presented here, justify the use of models that do not account for cell-cycle phenomena.…”
Section: Models For High-copy Plasmid Replicationmentioning
confidence: 67%
“…Because a culture of cells is not an amorphous mass of cytoplasm but a distribution of cells at various points of the cell cycle, and because many plasmids are known to attach to the cell membrane either loosely or to perform functions like partition and replication, such models should be used with caution. The results of membrane-elution experiments for high-copy plasmid replication during the cell cycle (Keasling et al, 1991(Keasling et al, , 1992bLeonard and Helmstetter, 1988;Zeuthen et al, 1972) and models, such as the one presented here, justify the use of models that do not account for cell-cycle phenomena.…”
Section: Models For High-copy Plasmid Replicationmentioning
confidence: 67%
“…That replication of the P1 prophage is altered by the presence of the minichromosome and the mini-R6K plasmid is unlikely. The timing of chromosome replication initiation (or the cell size at initiation of chromosome replication) is unaffected by the presence of the minichromosome (14), the F plasmid (10), and/or the R6K plasmid (11). Furthermore, the F plasmid and the R6K plasmid have the same replication patterns when they are alone in a cell as they do when they are present with the minichromosome in a cell (10,11).…”
Section: Discussionmentioning
confidence: 85%
“…The replication pattern of the high-copy plasmids has been consistently found to be cell-cycle independent (10,11,15,21), whereas the replication pattern of the low-copy plasmids (F, P1, and Rl) has been controversial. Recently, the contradictory reports of F plasmid replication were resolved by using the membrane-elution technique and quantitative measurement of label incorporated into plasmid DNA in cells grown at different rates (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fis binding to the numerous sites in the ␥ origin early in the cell cycle might block binding, which is essential for ␥-origin function (60). While studies have shown that an R6K replicon producing wt containing the ␥ and ␤ origins replicates continuously throughout the cell cycle (43,44), it remains unknown if replication of the isolated ␥ origin driven by copy-up is affected by the cell cycle and concomitant variations in Fis levels.…”
Section: Discussionmentioning
confidence: 99%